Financial distress, earnings management and Big 4 auditors in emerging markets - Viana, D. B. C., Jr.; Lourenço, I.; Black, E. L. (Accounting Research Journal, 2022)
The purpose of this study is to examine the association between financial distress and accruals-based earnings management in emerging markets, and the role that auditors play in that association. Design/methodology/approach: This study relies on a sample of 33,455 firm-year observations from 20 emerging markets, covering a large period of analysis of 20 years. A multivariate analysis is performed by considering the level of financial distress as the dependent variable, and the accruals-based earnings management and dummies for the type of auditor as the main independent ones. Findings: The authors predict and find empirical evidence that firms facing greater financial distress engage in income-increasing accruals-based earnings management in emerging markets, and that such engagement is lower in firms audited by Big 4 firms compared to those audited by non-Big 4 auditors. The authors also find significant differences across Big 4 audit firms in their role of constraining income-increasing earnings management strategies in firms with high levels of financial distress. Originality/value: The study adds to previous literature by investigating the association between financial distress and accruals-based earnings management in a comprehensive sample of 20 emerging markets, by providing important overall cross-country empirical evidence that has not been addressed by previous literature. The authors also bring new knowledge by discussing the role played by the Big 4 audit firms in limiting earnings management practices by firms with high levels of financial distress. Such a limitation serves as an important external corporate governance mechanism to restrain managers’ opportunistic behaviour in firms facing financial distress – especially in emerging economies characterized overall by institutional voids.